Pengaruh Latar Belakang Pendidikan Orang Tua dan Intensitas Perhatian Orang Tua terhadap Prestasi Belajar Siswa Kelas 2 SMU 1 Panggang Gunungkidul - Walgiyanti Walgiyanti; Esti Setiawati (Proceedings Series on Social Sciences & Humanities, 2022)
The purpose of conducting this research is to find out (1) Data on the educational background of parents of grade 2 SMU 1 Panggang, Gunungkidul, (2) Data on the intensity of parental attention of students in grade 2 SMU 1 Panggang, Gunungkidul, (3) Achievement student learning at SMU 1 Panggang, Gunungkidul, (4)The effect of educational background on student achievement in grade 2 at SMU 1 Panggang, Gunungkidul, (5) The effect of the intensity of parental attention on student achievement at SMU 1 Panggang, Gunungkidul, (6) The effect educational background of parents and the intensity of parental attention to parental learning achievement on learning achievement at SMU 1 Panggang, Gunungkidul. The population is 2nd grade students of SMU 1 Panggang, Gunungkidul which consists of 3 classes with a total of 116 students, all populations are taken as research respondents. The data collection method used is the questionnaire/questionnaire method and the documentation method. Data analysis was carried out by descriptive statistical analysis, partial correlation and multiple correlation. The results of the study are as follows: (1) The educational background of parents (X1) is 48,39% (2) the intensity of parental attention (X1) is 73.28% is in the medium category,(3)Student achievement in grade2SMU1Bakedat 100.00% is in the medium category, (4) There is a significant positive effect of parents' educational background and the intensity of parental attention on student achievement at SMU 1 Panggang, Gunungkidul. This means that the higher the educational background of parents and the intensity of parental attention, the higher the student's learning achievement, (5) the educational background of parents and the intensity of parental attention together make an effective contribution to learning achievement by 36, 261%.